DISTANCE LEARNING AS A FACTOR IN TEACHERS' PROFESSIONAL BURNOUT (Psychology Travelogs, 2025)
The article presents the results of a theoretical analysis and empirical study of the impact of distance learning on the development of professional burnout of higher education teachers. The aim of the study was to examine the peculiarities of teachers' professional burnout in the context of the specifics of distance work, in particular, to identify differences in the levels of emotional exhaustion, depersonalization and reduction of personal achievements among teachers working in a distance format and those using a full-time and/or blended learning format.Based on the analysis of scientific sources, it is proved that distance learning is a significant factor contributing to the growth of professional burnout among higher education teachers. In particular, teachers who work in a distance format demonstrate higher rates of emotional exhaustion, depersonalization and lower professional achievements compared to their colleagues who work in a full-time and mixed format. It was found that the main reasons for this phenomenon are isolation, technical difficulties, blurred boundaries between work and private life, and lack of social support. The results of the study indicate the need to introduce psychological support programs for teachers aimed at developing stress resistance, improving emotional well-being and maintaining professional well-being. Particular attention should be paid to measures to reduce emotional exhaustion, develop communication skills and optimize workload. The results of the study can be useful for specialists to improve educational policy to ensure comfortable working conditions for teachers during distance learning and for practical psychologists to develop and implement psychological support programs for teachers of higher education institutions.We see prospects for further research in the study of ways and means to prevent professional burnout of higher education teachers in the context of distance learning.
Keywords: distance learning; professional burnout; teachers; emotional exhaustion; psychological support